Circumventing 'free care' and 'shouting louder': using a health systems approach to study eye health system sustainability in government and mission facilities of north-west Tanzania. Issue 1 (December 2016) - Palmer, Jennifer; Gilbert, Alice; Choy, Michelle; Blanchet, Karl
Abstract Background Little is known about the contributions of faith-based organisations (FBOs) to health systems in Africa. In the specialist area of eye health, international and domestic Christian FBOs have been important contributors as service providers and donors, but they are also commonly critiqued as having developed eye health systems parallel to government structures which are unsustainable. Methods In this study, we use a health systems approach (quarterly interviews, a participatory sustainability analysis exercise and a social network analysis) to describe the strategies used by eye care practitioners in four hospitals of north-west Tanzania to navigate the government, church mission and donor rules that govern eye services delivery there. Results Practitioners in this region felt eye care was systemically neglected by government and therefore was 'all under the NGOs', but support from international donors was also precarious. Practitioners therefore adopted four main strategies to improve the sustainability of their services: (1) maintain 'sustainability funds' to retain financial autonomy over income; (2) avoid granting government user fee exemptions to elderly patients who are the majority of service users; (3) expand or contract outreach services as financial circumstances change; and (4) access peer support for problem-solving and advocacy. Mission-based eye teams had greater freedom to increase their income from user fees by not implementing government policies for 'free care'. Teams in all hospitals, however, found similar strategies to manage their programmes even when their management structures were unique, suggesting the importance of informal rules shared through a peer network in governing eye care in this pluralistic health system. Conclusions Health systems research can generate new evidence on the social dynamics that cross public and private sectors within a local health system. In this area of Tanzania, Christian FBOs' investments are important, not only in terms of the population health outcomes achieved by teams they support, but also in the diversity of organisational models they contribute to in the wider eye health system, which facilitates innovation.